Characterization of phytoplankton productivity and bio-optical variability in a polar marine ecosystem. (July 2021) - Kerkar, Anvita U.; Tripathy, Sarat C.; Hughes, David J.; Sabu, P.; Pandi, Sudarsana Rao; Sarkar, Amit; Tiwari, Manish
Graphical abstract: Highlights: Primary production (PP) was linked to in-situ absorption properties in the ISSO. Phytoplankton absorption (aph ) was a better predictor of PP than chlorophyll-a. ISSO PP models may need to account for intra-regional variation in aph and a*ph . Abstract: Knowledge of Southern Ocean carbon cycling is limited by a paucity of phytoplankton primary productivity (PP) and spectral absorption data in this globally-important region. We measured 13 C-based PP in the Indian sector of Southern Ocean (ISSO) during austral summer 2017, examining its link with spectral absorption coefficients and phytoplankton size structure derived from an absorption-based global model. Phytoplankton productivity was assessed at both coastal (60°S-69°S) and frontal stations (40°S-60°S), characterized by silicate- replete and -deplete water masses, respectively (indicated by measured nutrient ratios) to capture a range of phytoplankton growth conditions. Bio-optical relationships were used as indicators of phytoplankton community size structure and to assess the extent of cellular pigment packaging - a phenomenon reported previously for phytoplankton in this region. Blue-Red (B/R) ratios of phytoplankton absorption (aph ) spectra indicated that microphytoplankton (more prone to "package effects") were the dominant size class at most sites sampled. Overall, PP was better explained by aph ( R 2 = 0.85) than total chlorophyll-a ( R 2 = 0.64) in surface waters. The a*ph (675)-chlorophyll-a relationship explained package effects more effectively in frontal regions ( R 2 = 0.63) than stations further south ( R 2 = 0.30). The global absorption-based model captured smaller (pico, nano) phytoplankton size classes but failed to identify larger microphytoplankton, underscoring the need for region-specific algorithm modifications. Our findings improve existing understanding of spatio-temporal trends in PP and bio-optical variability within the Indian Sector of the Southern Ocean (ISSO) – knowledge that is essential to improve capacity to retrieve PP from satellite-based models in this region.